Research on the relationship between social support and academic self-efficacy among college students: a multivariate empirical analysis - Chen, Chunmei; Zhu, Yujie; Xiao, Fanghao (Frontiers in Public Health, 2025)
BackgroundThe critical role of social support in college students’ academic development cannot be ignored. This study aims to analyze the interrelationships and potential mechanisms between social support, sense of security, family cultural capital and academic self-efficacy.MethodsA multivariate moderated mediation model was constructed by surveying 1,119 college students using the Social Support Scale, the Sense of Security Scale, the Academic Self-efficacy Scale, and the Family Cultural Capital Scale.Results(1) social support significantly increases sense of security; (2) sense of security significantly enhances academic self-efficacy; (3) social support directly contributes to academic self-efficacy; and (4) sense of security partially mediates the relationship between social support and academic self-efficacy; (5) family cultural capital plays a moderating role in the effects of social support on academic self-efficacy, especially in the first half of the direct and indirect effects.ConclusionThese findings could provide an important theoretical basis and practical guidance for further understanding and enhancing academic self-efficacy among college students.